Development of a digital version of the Mini-Mental State Examination for children: a multidisciplinary study - Awawdeh, Letícia Cardoso Mendonça Mustafá; Rodrigues, Sandra Souza; Santos, Juliana Nunes; Morais, Rosane Luzia de Souza; Ferreira, Fernanda de Oliveira; Corrêa, Evelyn Daynnara Miranda; Pereira, Ana Alice Aparecida Sales; Fernandes, Amanda Cristina (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10967, 2025)
Introduction: Cognitive assessment of children is essential to identify deficits and plan appropriate interventions. Objective: This paper presents the development of a digital version of the Mini-Mental State Examination for Children (MMC), aiming to make it more accessible to children with motor impairments, such as those with cerebral palsy. Methodology or Steps: Using a simple lifecycle model (discovering requirements, designing alternatives, prototyping, and evaluating), a high-fidelity prototype was created. Results: Testing showed strong acceptance among healthcare professionals, with 100% considering the content appropriate and an average System Usability Scale (SUS) score of 85, indicating good usability. The digital version improves accessibility, reduces motor barriers, and enhances result standardization.